"Doing Fear": The Influence of Hetero‐femininity on (Trans)women's Fears of Victimization. Issue 4 (13th September 2013) - Yavorsky, Jill E.; Sayer, Liana
Abstract : Through 26 in‐depth interviews with male‐to‐female transsexuals (transwomen), this study examines transwomen's perceptions of safety, pre‐ and post‐transition. The majority reported higher levels of fear and believed they would be unable to fight off an attacker post‐transition even though most were large statured and were socialized as males. Exposure to heterosexual practices and to cultural messages depicting women as physically weak and sexually vulnerable, and transwomen's embodiment of hetero‐femininity play a central role in increasing their fears. Their experiences as women are powerful enough to override decades of prior male experiences and expose the socially constructed nature of fear and bodily agency.